Modeling and stability enhancement of a permanent magnet synchronous generator based DC system for More Electric Aircraft - Yang, Jiajun; Yan, Hao; Gu, Chunyang; Wang, Shuo; Zhao, Weiduo; Wheeler, Patrick; Buticchi, Giampaolo (Institute of Electrical and Electronics Engineers Inc., 2021)
The concept of the More Electric Aircraft (MEA) is aimed at electrifying the mechanical, hydraulic, and pneumatic subsystems on aircraft. With increasing usage of power electronics, the architecture of on-board electrical power distribution systems (EPDS) becomes more complicated. Therefore, it is necessary to analyze the stability of the system. This paper firstly presents and validates an impedance model of a permanent magnet synchronous generator (PMSG) as a source and dual active bridge (DAB) converter as a load. These models are used for the stability analysis of a simple DC power system. In addition, two new control strategies are proposed to enhance the stability of the system. The stabilization effects of the new control strategies are verified with experimental results.